Chinese religion in Malaysia: temples and communities - Tan, Chee Beng (Chinese overseas, 2018)
Temples and local communities -- Deities, speech groups, and temples -- Temple services, mediums, and temple promotion -- Localization and Chinese religion -- Pudu: the hungry ghosts festival -- Religious organizations and philanthropy -- Taoist religion in Malaysia